Etos Kerja Islami: Studi pada Usaha Jasa Loundry di Pontianak - Lusi Rahma; Rafli Al Kautsar; Suci Rahmadani; Ainun Zehriyah (CV Global Research Publication, 2025)
This study explores the application of Islamic work ethics in the management of “New Loundry,” a Loundry service business based in Pontianak, Indonesia. Islamic work ethics emphasize not only professionalism and productivity but also the spiritual dimension of work, which includes values such as worship, trust (amanah), sincerity, and honest livelihood. Using a qualitative case study approach, data were collected through interviews with the business owner and employees, direct observation, and documentation. The study found that “New Loundry” integrates Islamic principles in its daily operations, including honesty in transactions, discipline in fulfilling responsibilities, and maintaining a halal income. Employees are encouraged to view their work as a form of worship and moral duty, while the employer ensures fair wages, appropriate working conditions, and spiritual support. Additionally, the business avoids unethical practices such as fraud, usury (riba), and exploitation. These implementations contribute not only to the business’s operational efficiency and employee satisfaction but also to customer trust and long-term sustainability. The findings suggest that embedding Islamic ethical values in small business management can foster a more holistic approach to success—one that balances material achievement with spiritual well-being. This study offers a model for other small businesses aiming to operate ethically within an Islamic framework.